1977
DOI: 10.1126/science.199942
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific and Nonstereospecific Effects of (+)- and (—)-Morphine: Evidence for a New Class of Receptors?

Abstract: The unnatural (+) enantiomer of morphine had minimal activity in three opiate assays in vitro: the rat brain homogenate binding assay, the electrically stimulated guinea pig ileum assay, and the inhibition of adenylate cyclase in neuroblastoma X glioma hybrid cell homogenates. When (+)-morphine was microinfected into the periaqueductal gray (a site known to mediate morphine analgesia) of drug-naive rats, there was only minimal analgesia, but the hyperresponsivity usually observed after microinfection of (-)-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(45 citation statements)
references
References 30 publications
3
40
1
1
Order By: Relevance
“…(−)-Morphine interacts with µ-opioid receptors to produce potent antinociception and other pharmacological effects. On the other hand, the dextrorotatory (+)-morphine, which is synthesized from sinomenine (Iijima et al, 1978a), does not have any affinity for µ-opioid receptors and therefore does not produce any µ-opioid receptor mediated pharmacological effects (Jacquet et al, 1977). However, we have previously demonstrated that (+)-morphine pretreated spinally attenuates the antinociception produced by spinally-administered (−)-morphine in the mouse.…”
Section: Introductionmentioning
confidence: 97%
“…(−)-Morphine interacts with µ-opioid receptors to produce potent antinociception and other pharmacological effects. On the other hand, the dextrorotatory (+)-morphine, which is synthesized from sinomenine (Iijima et al, 1978a), does not have any affinity for µ-opioid receptors and therefore does not produce any µ-opioid receptor mediated pharmacological effects (Jacquet et al, 1977). However, we have previously demonstrated that (+)-morphine pretreated spinally attenuates the antinociception produced by spinally-administered (−)-morphine in the mouse.…”
Section: Introductionmentioning
confidence: 97%
“…Although the analgesic effect of l-morphine is believed to be mediated through the mu-opioid receptor, whether the effects of the receptor antagonists naloxone and naltrexone are mediated through the mu-opioid receptor remains controversial. Therefore, we used both l-morphine, which has a high affinity to the mu-opioid receptor, and its synthetic enantiomer d-morphine, which does not bind to the mu-opioid receptor (25), to explore the underlying molecular mechanism of the protective effect of morphine on DA neurons in two in vitro models of PD. In this study, we show that subpicomolar concentrations of both lmorphine and d-morphine significantly down-regulate LPS-or 1-methyl-4-phenylpyridinium (MPP ϩ )-induced microglia activation with similar efficacy, clearly showing that the cellular mechanism of morphine-mediated neuroprotection is independent of the mu-opioid receptor pathway.…”
Section: P Arkinson's Disease (Pd)mentioning
confidence: 99%
“…The synthetic dextro-enantiomer of levo-morphine has minimal activity in the -opioid receptor binding assay, the electrically stimulated guinea pig ileum assay, and the inhibition of adenylate cyclase activity in the neuroblastoma ϫ glioma hybrid cell homogenates, indicating that it does not interact with -opioid receptors (Jacquet et al, 1977). Unlike levo-morphine, which produces potent levo-naloxone reversible analgesia, dextro-morphine microinjected into the periaqueductal gray in rats produces minimal analgesia (Jacquet et al, 1977). In the present study, i.t.…”
Section: Introductionmentioning
confidence: 99%